PERLINDUNGAN HUKUM TERHADAP NASABAH GAGAL BAYAR DALAM PERJANJIAN JUAL BELI MEDIUM TERM NOTES DARI ASPEK HUKUM PERDATA DAN HUKUM PIDANA - Sherly Angelina Chandra; Keyzia Betarli Lengkong; Jenny Lim (Program Magister Ilmu Hukum Universitas Pancasila, 2021)
Various financial instruments in Indonesia has grown rapidly in recent years, one of them isMedium Term Notes. But in fact, same with other type of investments, Medium Term Notes also hasvarious risks, one of them is when investment companies are not responsible so they fail to pay theinvestors. The urgency of law protection for investors who experience default because of MediumTerm Notes is very important considering the losses and disadvantage suffered by investors. Thispaper uses a normative juridical research method that conducts literature review, which useslibrary materials or secondary data through primary legal materials and secondary legal materials.The results of this research show that investors who experience default because of Medium TermNotes can sue to investment companies in terms of criminal law or civil law